1987
DOI: 10.1016/0014-5793(87)81167-5
|View full text |Cite
|
Sign up to set email alerts
|

The initial phase of GnRH‐stimulated LH release from pituitary cells is independent of calcium entry through voltage‐gated channels

Abstract: Kinetic studies on gonadotropin-releasing hormone (GnRH)-stimulated luteinizing hormone (LH) release were undertaken using rat and chicken pituitary cell cultures. In response to continuous GnRH stimulation, a biphasic pattern of LH release was demonstrated.The two phases showed different susceptibility to the voltage-gated Ca*+ channel blockers D600 and nifedipine. The first (transient) phase of LH release was unaffected by the Ca*+ channel blockers whereas the second (sustained) phase was inhibited by both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…However, the following should be noted. LH release has been shown to be partially or completely dependent on Ca2+ influx (2,19). This Ca2+ influx apparently involves L-type channels (19,28), although there is also some disagreement on this point (2,29).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the following should be noted. LH release has been shown to be partially or completely dependent on Ca2+ influx (2,19). This Ca2+ influx apparently involves L-type channels (19,28), although there is also some disagreement on this point (2,29).…”
Section: Methodsmentioning
confidence: 99%
“…LH release has been shown to be partially or completely dependent on Ca2+ influx (2,19). This Ca2+ influx apparently involves L-type channels (19,28), although there is also some disagreement on this point (2,29). However, recent studies, which monitored LH release on a relatively rapid time base, indicated that L-channel blockers did not block an initial spike of LH release but did block subsequent release over an extended time course (19).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations